IMPROVING THE MONETARY POLICY EFFECTIVENESS BY EVALUATING ITS EFFECTS ON CREDITING THROUGH SECTORALLY CALIBRATED MONETARY TRANSMISSION CHANNELS - Дейсан, Ігор (Socio-economic relations in the digital society, 2020)
This paper examines the effect of the monetary transmission mechanism in the cross-sectoral context. The transmission mechanism from refinancing rate, liquidity and hryvnia exchange rate against the U.S. dollar to sectoral lending and economic activity was studied using a structural VaR-model. A significant heterogeneity in the response of sectoral indicators was found, which should be taken into account by the National Bank of Ukraine when setting up monetary policy. Changes in central bank reference rate do not affect short-term household rates, when changes in banking system liquidity widely affect retail rates - the most sensitive are credit rates for financial institutions, households, trade sector and industry. For the purpose of government bond rate reduction, both the refinancing rate and the change in free liquidity are effective. Liquidity growth stimulates short-term lending to non-financial corporations, but changes in lending rates do not affect lending volumes.
Keywords: transmission mechanism of monetary policy; sectors of economy; credit rates; lending volumes